2019
DOI: 10.3390/en12081463
|View full text |Cite
|
Sign up to set email alerts
|

On the Linkage between the Energy Market and Stock Returns: Evidence from Romania

Abstract: his paper aims to establish whether the Romanian energy market has an influence on the good running of the associated capital market. In order to achieve this objective, we approached a series of econometric techniques that allowed us to study the cointegration between variables, the presence of short-term or long-term causality relationships, and the application of impulse-response functions to analyze how the BET index responds to the shocks applied. The empirical findings from the Johansen cointegration tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…They find that oil price changes have asymmetrical effects on renewable energy stock prices in the short-run but not in the long-run. Moving further, another study confirmed both the existence of a long-and short-term relationship between the Romanian energy market and the capital market using, among others, an ARDL model, on the basis of a mixture between stationary and non-stationary time series [39]. In addition to this, another research found that in the long-run oil price, similar to interest rates and real effective exchange rates, has a negative impact on Malaysia's stock returns, while industrial production has a positive impact [40].…”
Section: Methodsmentioning
confidence: 82%
“…They find that oil price changes have asymmetrical effects on renewable energy stock prices in the short-run but not in the long-run. Moving further, another study confirmed both the existence of a long-and short-term relationship between the Romanian energy market and the capital market using, among others, an ARDL model, on the basis of a mixture between stationary and non-stationary time series [39]. In addition to this, another research found that in the long-run oil price, similar to interest rates and real effective exchange rates, has a negative impact on Malaysia's stock returns, while industrial production has a positive impact [40].…”
Section: Methodsmentioning
confidence: 82%
“…This study aims to investigate the multiple causes and theories connecting these crucial components of the global economy. Crude oil serves as a vital energy source for transportation, electricity generation, and diverse industrial applications, making it indispensable to the global economy (Armeanu et al, 2019;Cao et al, 2020). Factors such as supply and demand dynamics, geopolitical tensions, market speculation, and global economic conditions intricately influence crude oil prices.…”
Section: Introductionmentioning
confidence: 99%